E-Book Development Effectiveness Problem Based Learning with Quizing in Physics Learning - Irena Retno Damayanti; Yohandri Yohandri (Postgraduate, University of Mataram, 2022)
This research was based on observations made at one of the Dhamasrya public schools, SMAN 1 Koto Baru, which found several shortcomings in the learning system carried out, one of which was the lack of variation in the learning carried out and the lack of teaching materials based on the 2013 curriculum in study. The formulation of the problem that can be given is how to develop an E-Book Based on Problem Based Learning. Accompanied by Giving Quizzes to Class X High School Physics Learning. This research belongs to research with the type in this research is Research and Development and the development model used is the Plomp development model. The development analysis uses the stages of validation, practicality and effectiveness. Assessment of effectiveness using knowledge assessment test sheets, self-assessment for attitudes and skills assessment for performance and the N-Gain value of the achievement of student competencies. Analysis of the effectiveness using the N-Gain value and completeness of students who are above 80% of all students. The results obtained in this study are a product in the form of an E-Book Based on Problem Based Learning Accompanied by Giving Quizzes to Class X High School Physics Learning that is effective for use by students and for use by teachers. Analysis of the effectiveness assessment using cognitive learning outcomes with almost all completeness results or 80% of students who participated in the study were declared complete. The results of the affective assessment carried out using the self-assessment sheet obtained results in a good category and psychomotor learning outcomes assessed using the worksheets obtained results in a good category. In addition, using the N-Gain equation obtained high scores. Based on the results obtained, the developed E-Book can be declared effective.